Penggunaan media audio visual dalam pembelajaran tema 2 “menyayangi tumbuhan dan hewan” di kelas III sekolah dasar - Agita Khoirunnisa Rusadi; Chumdari Chumdari; Suharno Suharno (Didaktika Dwija Indria, 2023)
This study aimed to describe the steps of using audiovisual media in thematic learning, the factors that influence the use of audiovisual media in thematic learning, and the effectiveness of thematic learning through audiovisual media. This method used a descriptive qualitative research method through a case study approach. Data collection techniques used are interviews, checklists, questionnaires and documentation studies. The research subjects were directors, teachers and students. Test the validity of the data using triangulation techniques, sources and time. The data analysis of this research used the Miles and Huberman interactive analysis technique, which consisted of data reduction, data presentation, and verification/inference. The results of this study indicate that the implementation of audiovisual media in learning 2nd theme "Menyayangi tumbuhan dan hewan" of 3rd grade of SD Ta'mirul Islam Surakarta is according to the steps in using audiovisual media. The factors that affect the use of audiovisual media in learning are divided into two. The use of audiovisual media makes learning more effective because the learning process attracts students' attention, achieves learning objectives and increases student learning success.